A new species of the genus Arachnothelphusa Ng, 1991 (Crustacea: Decapoda: Gecarcinucidae) from a limestone cave in Sarawak (Malaysian Borneo) - Jongkar, Grinang; Ng, Peter K. L. (National University of Singapore, 2021)
A new species of cavernicolous gecarcinucid crab, Arachnothelphusa sarang, is described from a limestone cave in northern Sarawak, Malaysian Borneo. This increases the number of Arachnothelphusa species to six. It is the second member in the genus that is known to primarily occupy limestone caves, the other being A. rhadamanthysi Ng & Goh, 1987, from Gomantong in Sabah. Both species appear to be cavernicolous species with pale body colouration in life.